2019
DOI: 10.7759/cureus.5231
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Coronary Artery Dissection Secondary to Rheumatological Diseases: A Comprehensive Review

Abstract: Spontaneous coronary artery dissection (SCAD) is a life-threatening condition and multiple conditions have been associated with this entity. This study aims to further investigate and characterize the association of the underlying rheumatological disease with SCAD. A comprehensive literature search on four databases was performed using different Medical Subject Headings (MeSH) and all articles on SCAD in association with rheumatological diseases were identified. The analysis was performed using the Statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…11 Ullah et al conducted a systematic review of 10 articles about SCAD associated with rheumatologic conditions and found that many cases were associated with systemic lupus, most patients presented with non-ST elevation myocardial infarction involving the left main coronary artery, and the majority were managed with stenting. 15 Mortality was <20%.…”
Section: Discussionmentioning
confidence: 96%
“…11 Ullah et al conducted a systematic review of 10 articles about SCAD associated with rheumatologic conditions and found that many cases were associated with systemic lupus, most patients presented with non-ST elevation myocardial infarction involving the left main coronary artery, and the majority were managed with stenting. 15 Mortality was <20%.…”
Section: Discussionmentioning
confidence: 96%
“…Ullah et al systematically reviewed 10 articles about SCAD associated with rheumatologic conditions and found that many cases were related to systemic lupus. Furthermore, most patients presented with non-ST elevation myocardial infarction involving the left main coronary artery [ 48 ]. SCAD is an underdiagnosed disease that requires a high index of suspicion.…”
Section: Reviewmentioning
confidence: 99%
“…Pada penelitian kohort eropa dengan populasi besar didapatkan 45% berhubungan penyakit fibromuscular dysplasia (FMD) dan PHACTR1 dikonfirmasi sebagai genetik yang berhubungan dengan SCAD [16]. Penelitian rheumatologi didapatkan Lupus Eritematosus Sistemik (LES) yang paling berkaitan dengan SCAD [17]. SCAD juga memiliki hubungan terhadap beberapa penyakit FMD, gagal ginjal kronis, peripheral artery disease (PAD), carotid artery disease [18].…”
Section: Patofisiologiunclassified